Gastropods Species Associated with Seagrass Ecosystems in Pasir Putih, Manokwari - Duijesisca Gultom; Abdul Hamid A Toha; Philipus Musyeri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Gastropods are one of the classes of mollusks that associate well with seagrass ecosystems. The waters of Pasir Putih are included in a coastal area where many types of gastropods are found in seagrass ecosystems. However, not all types of gastropods in seagrass beds in this region are well known. For this reason, this study aims to determine the types of gastropods associated with seagrass ecosystems in the waters of Pasir Putih, Manokwari. But specifically the objectives of this study are divided into 3, knowing the types of gastropods, seagrass species and the association of gastropods with seagrass in Pasir Putih Waters, Manokwari. In sampling, the quadratic transect method was used, drawn perpendicularly from the shore towards the shore. Physical parameters of water chemistry were observed in situ, this data collection method used was descriptive method. Based on the results of the identification that has been done, that there are 115 individuals, 42 species and 15 families that exist in the White Sand Waters, Manokwari. Four seagrass species were found, namely Cymodocea rotundata, Halodule pinifolia, Halophila ovalis, and Syringodium isoetifolium.